Delayed diagnosis of an infected vallecular cyst in an infant - Robert Hashemzadeh-Gargari; Samita M. Heslin; Richard Sidlow (Elsevier, 2018)
Vallecular cysts in newborns/infants are rare and frequently misdiagnosed. However, certain characteristics distinguish this entity from other common entities that are diagnosed in this age group. We present a case of a vallecular cyst in an infant initially diagnosed as laryngomalacia, and explore possible reasons why this case was initially misdiagnosed based on the etiologies and natural history of this uncommon pediatric upper airway problem. Keywords: Vallecula, Supraglottis, Neonatal